Perbandingan Efektivitas Mikroba Hasil Rekayasa Genetik dan Mikroba Alami dalam Bioremediasi Polutan Lingkungan : kajian literatur: Comparison of Effectiveness of Genetically Engineered Microbes and Natural Microbes in Bioremediation of Environmental Pollutants: a literature review - Neva Afifah Putri Suharja; Fadly Hidayaturochman; Tsabitna Amalia Ihsani (Jurnal Biodiversitas dan Bioteknologi, 2025)
Environmental pollution is becoming an increasingly pressing issue, threatening human health, ecosystems and the sustainability of natural resources. Genetically modified microbes are designed to have a higher degradation ability of harmful compounds compared to natural microbes, thereby increasing the efficiency of enzymes involved in this process. The objectives of this research include; analyzing the potential of genetically engineered microbes in degrading environmental pollutants, evaluating the efficiency and resistance of genetically engineered microbes and natural microbes in degrading environmental pollutants, examining the implications of using genetically modified microbes on environmental sustainability, ecosystem safety, and analyzing the GEO microbial control system post-bioremediation. The method of writing this literature review uses online-based literature searches with sources from Google Scholar, Pubmed and Sciencedirect. GEO microbes have the potential to degrade environmental pollutants and are superior to natural microbes. The advantages of GEO microbes in degrading environmental pollutants such as specificity, high efficiency, and environmentally friendly. GEO microbes are proven to be effective in degrading various pollutants. GEO microbes released into the environment to degrade pollutants are at risk of disrupting the balance of the environmental ecosystem. The population of GEO bacteria in the environment can be suppressed using composting and reducing the population of GEO bacteria.